Linguistics of the Qur’an in the Interpretation of Bintu Syathi - Yossi Kurnia Yudatama; Meirando Rukhuz (al-Afkar, Journal For Islamic Studies, 2024)
The linguistic study of the Qur'an is an important aspect in interpreting the Qur'ana because its scope is related to how a verse of the Qur'an is interpreted, Bintu Syati himself interprets the Koran from a linguistic perspective using the theory of antisynonymity and rejecting taraduf which in his analysis knife uses cross-reference theory. The research method used is a qualitative method based on books and journals (library review). The focus of this research is on the figure Aisyah Abdurrahman bintu Syathi’ and the theory she developed. The results of this research found that anti-synonymity theory views that there is no similarity in the meaning of lafadz lafadz in the Qur'an, each of which has its own meaning. The influence of Bintu Syathi's thoughts cannot be separated from the thoughts of Amin al-Khulli, her teacher and husband who also adhere to the theory of antisynonymity.